Association of AM fungi in important Pteridophytic plants of Maharashtra, India. - Sarwade, Prakash P; Shaikh, R U; Chandanshive, S S; Bhale, U N (International Multidisciplinary Research Journal, 2012)
Four pteridophytic plants were studied for their Arbuscular mycorrhizal (AM) fungal association. All tested plants were distributed in Maharashtra state. The result revealed that all the tested pteridophytic plants (viz. Equisetum spp, Marsilea spp, Nephrelepis spp, and Adiantum spp) had AM association in the roots and spore population in the soil. However, maximum root colonization was observed in Equisetum spp (96%) where as minimum was observed in Nephrelepis spp (28%). Equisetum spp (208) showed more spore density where as less in Adiantum spp (27). Total 15 AM fungal species were identified and quantified in which Glomus spp were dominant followed by Acaulospora spp Sclerocystis spp and Gigaspora spp were found less frequently distributed.